2014
DOI: 10.1039/c3nr06692d
|View full text |Cite
|
Sign up to set email alerts
|

Metal-seeded growth of III–V semiconductor nanowires: towards gold-free synthesis

Abstract: Semiconductor nanowires composed of III-V materials have enormous potential to add new functionality to electronics and optical applications. However, integration of these promising structures into applications is severely limited by the current near-universal reliance on gold nanoparticles as seeds for nanowire fabrication. Although highly controlled fabrication is achieved, this metal is entirely incompatible with the Si-based electronics industry. In this Feature we review the progress towards developing go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
86
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 226 publications
4
86
0
Order By: Relevance
“…It has also been shown that solid NPs (Vapor-Solid-Solid, VSS) can aid the crystallization process, making the particle-seeded approach applicable to a rather wide range of growth parameters [6]. Further, Au NPs are not a prerequisite for fabricating NW structures as evident by the often used self-catalyzed method [8,9] and reports of using other foreign metal NPs [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that solid NPs (Vapor-Solid-Solid, VSS) can aid the crystallization process, making the particle-seeded approach applicable to a rather wide range of growth parameters [6]. Further, Au NPs are not a prerequisite for fabricating NW structures as evident by the often used self-catalyzed method [8,9] and reports of using other foreign metal NPs [10].…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of controlling and improving semiconducting nanowire (NW) devices for various applications1234567, an extensive research effort has been invested in studying NW growth; this was typically achieved by studying the different effects of user controlled parameters: (i) materials - including type and size of NW catalyst, the growth substrates and precursors, and (ii) by altering growth-system parameters, i.e., temperature and precursor flow891011121314151617. In the following report we present a new paradigm, that of catalyst shape engineering, as a useful tool to control NW growth results; in particular, we show that by imposing a non-hemispherical shape to the catalyst-substrate interface, anisotropic cross-sectioned NWs may be grown - NWs with potentially new physical characteristics.…”
mentioning
confidence: 99%
“…However, thin film epitaxy of InAsP/InAs(Sb) heterostructures, especially with high antimony or phosphorus composition, is challenging due to lattice mismatches, which might result in planar defects. Alternatively, heteroepitaxy with large lattice mismatch can be achieved by the bottom-up growth of vertical freestanding nanowires due to elastic deformation occurring at heterogeneous interfaces [9,10].…”
Section: Introductionmentioning
confidence: 99%